CYBER PUBLIC RELATIONS DALAM MEMBANGUN CITRA THE ASIAN POST - Dwi Rahma; Winda Dwi Astuti Zebua (Jurnal Ilmiah Multidisiplin Ilmu, 2025)
The role of Public relations has significantly shifted with the advancement of digital technology. The primary function of Public relations in building a corporate image has evolved into Cyber Public relations, which utilizes digital platforms. The Asian Post employs its website and Instagram to establish a positive image. As a relatively new media outlet, The Asian Post faces challenges in increasing audience traffic and gaining recognition amid competition with more established platforms. This study uses a descriptive qualitative approach by collecting data through in-depth interviews and image documentation. The analysis is based on Heath’s (2013) eight elements of Cyber Public relations. The purpose of this research is to explore how The Asian Post implements Cyber Public relations through the elements of Message, User Access, Electronic Publishing, Sharing Opinions and Suggestions, Networking, Collaboration, Instructions, and User Engagement in building a positive image. The findings show that The Asian Post applies Cyber Public relations strategies to enhance its image as a credible digital news platform. Messages are delivered through its website and Instagram, emphasizing data accuracy. User access is optimized through website navigation and Instagram features such as hashtags, highlights, and stories. Electronic publishing is carried out through an e-magazine released quarterly. Opinion sharing occurs through interactive content, although comment interaction remains low. Networking is strengthened through participation in digital communities and collaborations with various partners, including Jazz Gunung and Exco PSSI. Instructional content is provided through educational videos and live streaming discussing political and economic issues. User engagement is fostered through quizzes and promotional content that encourage audience participation.